Perkembangan Perbankan Syariah Sebelum dan Sesudah Spin-Off - Inal Kahfi (Departement of Mathematics Education, 2023)
In Article 68 of UUPS, Article 40 of PBI No. 11/10/ PBI/2009 it is explained that UUS is obliged to separate UUS into BUS if: (a) The asset value of UUS has reached 50% (fifty percent) of the total asset value of its parent BUK, (a) No later than 15 (fifteen) years since the enactment of Law Number 21 of 2008 concerning Islamic Banking. BUK that has a UUS can separate the UUS before the fulfillment of the conditions as referred to by fulfilling the requirements as stipulated in the Bank Indonesia turan Map. Spin-Off is a new institution regulated in Law No. 40 of 2007 concerning limited liability companies (Limited Liability Company Law) and Sharia Banking Law. In general, a Spin-Off describes an add-on or derivative product or derivative or the result of something imitation of a previous attempt. The term Spin-Off is often associated with the formation of a new company, in which including its new product is the same thing or a copy of the parent organization, and gives rise to new economic activity. This separation can take different forms, but generally requires important changes to the control, risk, and distribution of profits. Another element is the transfer of technology and ownership rights from the parent to the new owner. This study aims to determine and analyze the development of Islamic banking through the financial performance of Islamic banks before and after the Spin-Off.